Underlying histopathology of HIV-infected women with squamous cell abnormalities on cervical cytology - Nongyao Suwankanta (2018)
This study was undertaken to evaluate the underlying histopathology of HIV-infected women who had abnormal cervical cytology. HIV-infected women with abnormal cervical cytology undergoing colposcopy at Chiang Mai University Hospital between January 2001 and February 2008 were reviewed. The cohorts were matched and compared with an HIV-negative group. During the study period, 65 HIV-infected women with abnormal cervical cytology were available for review. The abnormal cervical smears were atypical squamous cell (9), low-grade squamous intraepithelial lesion (22), high-grade squamous intraepithelial lesion (27), and squamous cell carcinoma (7). When stratified by severity of abnormal cytology, HIV-infected women had a higher risk of having cervical intraepithelial neoplasia II or higher, whether the cervical smear showed low-grade (P=0.01) or high-grade abnormality (P=0.04) compared with the HIV negative group. After adjustment by age, parity, and menopausal status, HIV-infected women had 2.56 times the risk of having CIN II or higher (69.2% of HIV-infected women compared with 47.7% of HIV negative women; 95% CI=1.21-5.40, P=0.01). In conclusion, HIV-infected women with abnormal Pap smears are a population subset with higher risk of significant cervical lesions, irrespective of severity of abnormal cervical smears.